Motivations, experiences, and aspirations in patient engagement of people living with metastatic cancer - Patricia Stoop; Leslie Duran (The Beryl Institute, 2021)
The objective of this patient-led study was to explore the motivations, experiences, and aspirations of people living with metastatic cancer who volunteer in patient engagement. This qualitative study filled a gap in lived experience research about patient engagement by focusing on an oft ignored population - those living with metastatic cancer. We used a patient-oriented research approach throughout the research cycle from proposal development to data analysis. A Patient Partner helped develop the project proposal. We selected a qualitative descriptive design to best align with our patient-oriented research goals. The first author, a peer researcher with metastatic cancer, conducted semi-structured interviews with seven participants. The interview questions focused on why patients with metastatic cancer volunteered in patient engagement, the experiences and challenges they encountered as volunteers and what they wanted to achieve in their participation. The interviews were transcribed by the interviewer with personal details redacted for confidentiality. Optional member-checking occurred with three participants. After the interviews, two participants joined the research team to participate in data analysis and interpretation of the findings. Thematic analysis was used to identify common themes in the transcribed and redacted participant interviews. The resulting themes were contributing fully, creating a better cancer experience, making meaningful connections, giving back, and struggling with the system. These findings yielded theme-based advice for both patient partners and administrators for creating meaningful patient engagement. Further research led by patient partners could contribute to a more empowered patient engagement program. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.